A Weighted Markov Chain Application to Predict Consumer Price Index When Facing Pandemic Covid-19 - Indah Purnama Sari Siregar; Rina Widyasari; Nurul Huda Prasetya (Quadratic: Journal of Innovation and Technology in Mathematics and Mathematics Education, 2021)
Covid-19 is an infectious disease caused by acute respiratory syndrome coronavirus 2 (severe acute respiratory syndrome coronavirus 2 or SARS-CoV-2). It makes the decrease of people's purchasing power. Meanwhile, the economic growth indicates the success of a country's economic development. Therefore, the Consumer Price Index occurs Inflation and Deflation, which is commonly referred to in the economy as the Consumer Price Index. This study aimed to apply a weighted Markov chain method to predict the consumer price index in the future. The satisfactory results obtained by researchers in predicting the consumer price index are in, the chance is 84.34% and the 12th month has a 78.54% chance.